Preparation of sulfur reference materials that reproduce atmospheric particulate matter sample characteristics for XRF calibration. (9th May 2013) - Indresand, H.; White, W. H.; Trzepla, K.; Dillner, A. M.
Abstract : Energy‐dispersive X‐ray fluorescence (XRF) is an important tool used in routine elemental analysis of atmospheric particulate matter (PM) samples collected on polytetrafluoroethylene (PTFE) membrane filters. The method requires calibration against thin‐film standards of known elemental masses commonly obtained from commercial suppliers. These standards serve as a convenient and widely accepted interlaboratory reference but can differ significantly from samples in their chemical composition, substrate, and geometry. These differences can introduce uncertainties regarding the absolute accuracy of the calibration for atmospheric samples. Continuous elemental records of the US Interagency Monitoring of Protected Visual Environments (IMPROVE) PM monitoring network extend back to 1988. Evaluation of long‐term concentration trends and comparison with other networks demand a calibration that is accurate and precise compared with the uncertainty of the XRF measurement itself. We describe a method to prepare sulfur reference materials that are optimized for calibration of XRF instruments used to analyze IMPROVE PM samples. The reference materials are prepared by using the atmospheric form of the element, by reproducing the sample geometry, and by using the same substrate as in samples. Our results show that stable, pure, anhydrous, and stoichiometric deposits are collected onto the filter substrates, and furthermore, that the reference material masses are accurate and have acceptable uncertainty in the measurement range. The XRF response of the sulfur reference materials is similar to other commercial standards and is linear in the measurement range, and the slope of the multipoint calibration curve has very low uncertainty. These reference materials are valid for the calibration of XRF systems, and they bring improved transparency and credibility to the IMPROVE calibration. Copyright © 2013 John Wiley & Sons, Ltd.